BACKGROUND AND FACTORS OF MUSLIM IMMIGRATION TO THE COUNTRIES OF THE EUROPEAN UNION - Sergey V. Ryazantsev,; Marina N. Khramova,; Anna I. Tyshkevich, (Scientific Journal of Pedagogy and Economics, 2021)
The article analyzes the prerequisites, factors and consequences of immigration to the European Union from countries with a predominantly Muslim population. The main typological characteristics of the recipient countries of migrants from predominantly Muslim countries are highlighted. The problems studied in this article attract the attention of a wide range of specialists due to its relevance and at the same time due to the lack of any adequate answers to the modern challenges faced by the de facto multicultural societies of developed industrial countries. The results of consideration of the rights and freedoms of migrants in various EU countries are also important in scientific and practical terms. Special attention is paid to the analysis of the situation in Germany, as the most attractive country for migrants. In the context of the ongoing changes in the ethnodemographic structure of the population, the forecast of the number and gender and age structure of the Muslim population in Germany by 2050 is given. This forecast suggests that the population of Muslim origin in Germany will increase from 4.3 million in 2014 to at least 5.8 million by 2050. The increase will be achieved mainly due to a higher fertility rate than that of the Germans. According to the theory of E. Lee, the authors distinguish two groups of factors, "pushing factors" and "attraction factors", which contribute to the immigration of Muslims to more economically developed countries. The push factors in the countries of origin of migrants are mainly related to the unstable political situation, economic crises, and high unemployment, especially among the young population. Attracting factors are mainly related to the ability to receive certain economic preferences in the country of reception, to get educated, to have a stable income and medical care. Along with certain benefits, expressed in an increase in the share of the working-age population, Muslim migration also carries certain risks for EU countries: socio-cultural, religious, criminal, economic, political and geopolitical factors that can significantly affect the balance of political forces in the EU countries. The problems that arose with the adaptation and integration of Muslim migrants as a result of the largest migration crisis in the twenty-first century showed that the host country, in this case, the member States of the European Union, found themselves in a paradoxical situation. On the one hand, resolutions were prepared and adopted at the European level, and a set of measures was developed to accept migrants and provide them with financial and social assistance, which was expected to facilitate the process of adaptation and further lay the foundation for the assimilation of young Muslims. It was assumed that these steps will help, to some extent, to spread democratic values and principles for immigrants. On the other hand, in reality, the situation turned out to be much more complex and ambiguous, a number of EU States actually refused to accept migrants on their territories. The countries of the Visegrad group can be cited as an example. The split within the EU on migration issues calls the very existence of the European Union into question. This paper uses data from Eurostat, the International organization for migration, the German statistical office, the European Commission, the European Statistical Office, and a number of other reputable statistical agencies as input data. The material presented in the article does not contain information (information) related to state secrets of the countries of the European Union and the Russian Federation.